Hospital Infection Control Strategies , effectiveness of the role of nursing practices, laboratory diagnostics, and hospital management policies in preventing healthcare-associated infections (HAIs) - Ibrahem esa Yahya AL-esa; Abdullah Saeed Alhurtumi; Abdulaziz Muslih Sulhi Almutairi; Khalid Ebrahem Hussain Alfalige; Hamad Mohammed Alkusaybiri; Mohammed Khalifa Albeladi; Mohammed Basheer Alharbi; Abdulhameed shreef althagafi; Rabiah abdullah Bajammal; Sharifah Almuhib Ali Jaber; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Healthcare-associated infections (HAIs) pose a formidable challenge to modern healthcare systems, leading to increased morbidity, prolonged hospitalizations, heightened healthcare costs, and sometimes mortality. This paper explores the multifaceted strategies employed to combat HAIs, e6mphasizing the interrelated roles of nursing practices, laboratory diagnostics, and hospital management policies. Nursing practices are pivotal in infection prevention, as nurses implement essential protocols such as hand hygiene, aseptic techniques, and the appropriate use of personal protective equipment. These practices promote patient safety and foster a culture of infection prevention throughout healthcare settings. Concurrently, advances in laboratory diagnostics, including rapid microbial identification and susceptibility testing, empower healthcare providers to make timely and informed clinical decisions, thereby mitigating the spread of infections. Ultimately, effective hospital management policies provide the framework for a cohesive infection prevention strategy. This includes leadership commitment, resource allocation, staff training, and the establishment of interdisciplinary collaboration, which collectively enhance compliance with infection control measures. By synthesizing these critical components, healthcare organizations can significantly reduce the incidence of HAIs, improve patient outcomes, and foster a safer healthcare environment. The review emphasizes that robust infection control is not merely a series of isolated practices but a comprehensive approach that integrates nursing, laboratory, and management efforts to achieve sustained improvements in patient safety and quality of care.